ANALYZING THE KNOWLEDGE, INTERESTS, PERCEPTION OF THE MINIMALISM LIFESTYLE AMONG MUSLIM STUDENTS AT AN ECO-FRIENDLY SCHOOL IN KUALA LUMPUR, MALAYSIA - Mansurni Abadi; Wulandari Wulandari (International Conference on Social and Islamic Studies, 2021)
Eco-friendly schools are currently popular among Malaysian middle and upper classes. because they teach youngsters about minimalism and provide an eco-friendly learning environment. They teach children about minimalism and provide an eco-friendly learning environment. The trendy minimalist lifestyle is the opponent of overconsumption. In Islam, a minimalist lifestyle is considered as an effort to raise muslim knowledge of environmental issues while respecting Maqasid al-Sharia values (Hifz al-biah). In education, students' knowledge, perspectives, and interests determine overall understanding and acceptance of minimalism. 74 students from three Eco-high schools in Kuala Lumpur participated in our quantitative study, which was evaluated with SPSS 20. Respondents must be Muslim, and the majority are Malays. The questionnaire has four sections, one for demographics and three for factors. The study found high total average knowledge (Min=3.86, SP=.573), perception (Min 3.90, SP=.477), and curiosity (Min 3.86, SP=.573). The study found that pupils had good stage awareness. The majority of students believe that minimalism is the implementation of Zuhd (asceticism) that always feel Qanaah (always feel enough) and is vital to increasing awareness toward zero-waste.